GEOGRAPHICAL RELATIONS OF DARKLING BEETLES (COLEOPTERA: TENEBRIONIDAE) OF THE PALAEARCTIC TETHYS DESERT-STEPPE REGION WITH THE HISTORICAL REVIEW - G. M. Abdurakhmanov; M. V. Nabozhenko; A. G. Abdurakhmanov; Yu. Yu. Ivanushenko; M. G. Daudova (Юг России: экология, развитие, 2016)
Aim. The aim of the work is to analyze the geographic relationships of the family Tenebrionidae, which should be the basis of faunogenesis of the Tethys region of Palaearctic. Methods. The work is based on the material collected by the authors in the various regions of the Caucasus, the south of the European part of Russia, Kazakhstan and North Africa during 50 years (from 1961 to 2016), as well as the extensive literature data. We used the cluster analysis based on the Jaccard similarity coefficient which considers the positive coincidences for analysis the Tethys region tenebrionid faunas. Invasive species are not included in the analysis. Results. Extensive review of the history of study of Western Palaearctic Tenebrionidae from the mid-19th Century to the present day is given. The main directions of contemporary research are marked. Four hundred three genera of darkling beetles are distributed in the Tethys region including dendrophilous groups with tropical origin,  transpalaearctic  and  cosmopolitan  species,  that  represent  63%  of  all  known  Palaearctic  tenebrionid  genera (640 genera). Three quarters of them (304 genera or 75%) combining 5674 species include mainly xerophilous genera that are not found outside the region or presented only by very small number of species in the neighboring territories. Evidences of a common historical development of tenebrionid fauna appear in the 24 common widespread Tethys genera, which may be slightly spread beyond the boundaries, but have a very high diversity of species and infrageneric (probably a center of the origin) diversity within the Tethys region. The significant part (61%) of common Tethys genera, the high diversity of large Palaearctic genera of Tenebrionidae in the western and eastern parts of Tethys region, as well as the presence of complex of supralittoral relics of marine paleobassins (Western Tethys and Eastern Paratethys) from the genus Ectromopsis, indicates a single area of faunogenesis of darkling beetles, which is historically related with epicontinental Paleogene Tethys Ocean. Two super-regions (with western Tethys and eastern Tethys complexis of taxa) are allocated. These two regions are divided on several subregions which differ by high level of taxonomic diversity. The division is based on the analyses of species and generic abudance and level of an endemism. Claster analyses of common to the region genera, Tethys genera, common to the region species and the genus Blaps shows similarity of Anatolia and the Balkan region faunas; the Caucasus is similar to Iran. Two early allocated super-regions are more or less clearly revealed on all dendrograms. The Arabian Peninsula and North Africa have ancient relations with both super-regions based on the analyses of Tethys genera, and the Arabian Peninsula and the Middle East have ancient relations with both super-regions using analyses of all tenebrionid species of the Tethys region. Conclusion. The faunogenesis of several subregions of the Tethys region was formed as island type. Analysis of the distribution and taxonomic diversity of darkling indicates a long-time development of the tenebrionid fauna in coastal and island ecosystems of the Tethys Ocean, and later an independent prime of this fauna in different areas of the Tethys desert-steppe region with the retreat of ocean water, aridity and orogeny. At the same time, faunistic elements of relic type of Paleogene origin are preserved and evoluted in the mountain island forests in Anatolia, the Middle East and the Atlas with the Late Tertiary relict flora.